PENGARUH KOMPETENSI RENAISANS TERHADAP BUDAYA KERJA DAN KINERJA GURU SEKOLAH DASAR DI KOTA MAKASSAR - Sitti Nurbaya (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
The research aims to know and explained the effect of renaisans competence toward job culture; to know and explained the effect of renaisans competence toward performance; and to know and explained the effect of renaisans competence, through job culture toward performance by teacher in elementary school Makassar City. These research applied on elementary school Makassar City with population of honor teacher have the letter of description of Limited Contract Time on 8 district which amount 1.519 persons. Samples as amount 317 respondents used of Slovin formulation. Data from quesioner to analyzed in used of Structural Equation Model with AMOS 18. The result of research to found that the renaisans competence in direct have effect toward the job culture by teacher. The renaisans competence in direct have effect toward the performance by teacher. The renaisans competence indirect through job culture have effect toward the performance by teacher.